SINERGITAS DEWAN KEHORMATAN NOTARIS DAN MAJELIS PENGAWAS NOTARIS DALAM PEMBERIAN SANKSI ATAS PELANGGARAN KODE ETIK - EDELIN PATRICIA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Notaris Dr. Suprayitno, SH, MKn2. Notaris Dr. Henry Sinaga, SH, MKn3. Notaris Dr. Rudy Haposan, SH,MKn Amendment of the Notarial Honorary Council of the Extraordinary Congress of Banten Indonesian Notarial Association in 2015, The Central Honorary Council has the authority to give recommendation to dismiss the Notary with dishonorable dismissal to the Minister of Law and Human Rights as it is stipulated in Article 77, letter d of Law No. 30/2004.The synergy between the Notarial Honorary Council and the Notarial Supervisory Board can only be seen in the case of supervision and development. They prepare for the test for extraordinary member of the Indonesian Notary Association and the Examination of Notarial Code of Ethics, but not in imposing the sanction. Therefore, the Notarial Honoray Council is expected to examine the violation, followed by the decision of the Notarial Supervisory Board on the Code of Ethics violation based on the Notarial Act and the code of ethics based on the Notarial Code of Ethics.Keywords: Notarial Honorary Council, Notarial Supervisory Board, Sanction, Code of Ethics